The Effectiveness of Tax Incentives in Increasing Investment in the Manufacturing Sector in Indonesia - Yulianti Yulianti (Dhana, 2025)
This study aims to evaluate the extent to which the tax incentive policies implemented by the Indonesian government have been able to encourage increased investment in the manufacturing sector. Tax incentives such as tax holidays, tax allowances, and import duty exemptions have long been relied upon as fiscal instruments to attract investment and strengthen the competitiveness of domestic industry. However, the effectiveness of their implementation in the field remains questionable. This study used a descriptive qualitative approach, with data collection techniques through in-depth interviews with key informants, including industry players, fiscal officials, and academics. Data were also obtained through a documentary study of laws and regulations, ministerial annual reports, and publications from relevant institutions such as the Statistics Indonesia (BPS) and the Investment Coordinating Board (BKPM). The results indicate that tax incentives do have a positive impact on investment decisions, particularly for large-scale companies with adequate administrative capabilities and access to information. However, their utilization has not been optimal for small and medium-sized enterprises (SMEs) due to a lack of understanding of incentive mechanisms and the persistence of significant bureaucratic barriers. Furthermore, a gap in access was identified, with large companies tending to have easier access to incentives than small ones. This research recommends the need for more adaptive fiscal policy reforms, simplified procedures, digitized tax services, and increased outreach and technical assistance to businesses. This will enable tax incentive policies to be implemented more effectively, fairly, and have a tangible impact on strengthening the national manufacturing sector.